2009
DOI: 10.1096/fj.08-126458
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine regulation of T‐cell activation by ATP release and P2X7receptors

Abstract: T-cell activation requires the influx of extracellular calcium, although mechanistic details regarding such activation are not fully defined. Here, we show that P2X(7) receptors play a key role in calcium influx and downstream signaling events associated with the activation of T cells. By real-time PCR and immunohistochemistry, we find that Jurkat T cells and human CD4(+) T cells express abundant P2X(7) receptors. We show, using a novel fluorescent microscopy technique, that T-cell receptor (TCR) stimulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
312
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 269 publications
(331 citation statements)
references
References 57 publications
7
312
2
6
Order By: Relevance
“…This suggests that spatiotemporal dynamics of mitochondrial translocation within the cell can regulate PMN functions. Indeed, similar observations were made in T cells where the accumulation of mitochondria and panx1 at the immune synapse results in the physical proximity of the sites of ATP production and of ATP release, minimizing rate-limiting diffusion and thus facilitating rapid local purinergic signaling at the immune synapse (25)(26)(27)(28)43). Thus, we conclude that mitochondrial ATP production and the location of mitochondria relative to panx1 contribute to purinergic signaling in stimulated PMNs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This suggests that spatiotemporal dynamics of mitochondrial translocation within the cell can regulate PMN functions. Indeed, similar observations were made in T cells where the accumulation of mitochondria and panx1 at the immune synapse results in the physical proximity of the sites of ATP production and of ATP release, minimizing rate-limiting diffusion and thus facilitating rapid local purinergic signaling at the immune synapse (25)(26)(27)(28)43). Thus, we conclude that mitochondrial ATP production and the location of mitochondria relative to panx1 contribute to purinergic signaling in stimulated PMNs.…”
Section: Discussionsupporting
confidence: 80%
“…Recent work by others has shown that different sets of P2 receptors regulate Ca 2ϩ signaling in other cell types (29). P2X receptors function as ATP-gated ion channels that can facilitate Ca 2ϩ influx, and in T cells, P2X1, P2X4, and P2X7 receptors regulate influx of extracellular Ca 2ϩ and cell activation in response to T cell stimulation (27,28). PMNs express several members of the P2X receptor family in addition to the predominant P2Y 2 receptor (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of T cell receptors (TCR) results in rapid and robust release of ATP from lymphocytes, leading to P2X receptor-evoked responses, e.g., cell proliferation [60][61][62][63]. Initial studies suggested that TRC-promoted ATP release encompasses a conductive pathway (see Pannexins, further below), but a recent report by Tokunaga et al [38] suggested that the secretory pathway represents an additional source of ATP release in activated T cells.…”
Section: Cellular Release Of Nucleotides From the Secretory Pathwaymentioning
confidence: 99%
“…This group also showed that human erythrocytes exhibited mechanosensitive large conductance channel activity consistent with Panx1, and that red cells exposed to either high K + or hypotonic stress displayed enhanced ATP release and dye uptake, in a carbenoxolone-sensitive manner [150]. A number of studies followed indicating that pharmacological inhibitors of Panx1 reduced ATP release in a broad range of cells, including lung epithelial cells [151][152][153], hypoxic red cells [154][155][156], bovine ciliary epithelial cells [157], retina and trabecular meshwork (TM5) cells [158,159], skeletal muscle [160], taste bud cells [161], T lymphocytes [61,62,162], and human neutrophils [109]. Panx1 knockdown (siRNA or shRNA) reduced nucleotide release in hypotonic-stressstimulated airway epithelial cells [151,152], stretched cardiomyocytes [163], apoptotic T lymphocytes [162] and T cells undergoing HIV infection [164], TM5 cells [159], and astrocytes [165].…”
Section: Pannexinsmentioning
confidence: 99%
“…Likewise, (2) P2X7R can migrate to lipid raft domains. (3) Otherwise, during intracellular infections, PLD could be activated and could promote lysosome-parasitophorous vacuole fusion, leading to pathogen processing T cell responses [91]. Recently, Schenk et al showed that the increase of ATP levels at inflammatory sites affected the activation state of effector T cells, and the activation of P2X7R by ATP inhibited the function and stability of regulatory T cells [92].…”
Section: Lipid Pathways and The P2x7 Receptor In The Immune Systemmentioning
confidence: 99%